2022
DOI: 10.1002/ppul.25847
|View full text |Cite
|
Sign up to set email alerts
|

Association between idiopathic pulmonary hemosiderosis and celiac disease in pediatric patients: A scoping review of the literature over the past 50 years

Abstract: Introduction: Idiopathic pulmonary hemosiderosis (IPH) is a rare cause of diffuse alveolar hemorrhage, the mechanism of which is currently unknown. Nearly onethird of pediatric patients with IPH test positive for Celiac disease (CD) serology.Several hypothetical mechanisms have been proposed to unify the coexistence of these two entities, also referred to as Lane-Hamilton syndrome (LHS).Method: This manuscript is a scoping review of the medical literature. Medline, Embase, and PubMed Central databases were sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 81 publications
1
17
0
Order By: Relevance
“…Less than 20% of patients complained of any significant GI symptoms at the time of IPH diagnosis. Similar findings were also seen in pediatric patients with LHS [ 77 ]. Although malabsorption leading to developmental delay is common in children with LHS, this is rarely the case in adults [ 53 ].…”
Section: Reviewsupporting
confidence: 85%
See 1 more Smart Citation
“…Less than 20% of patients complained of any significant GI symptoms at the time of IPH diagnosis. Similar findings were also seen in pediatric patients with LHS [ 77 ]. Although malabsorption leading to developmental delay is common in children with LHS, this is rarely the case in adults [ 53 ].…”
Section: Reviewsupporting
confidence: 85%
“…The fact that the prevalence is so high in children and adults, and the number is significantly higher than the general population, raises concerns for unifying the underlying pathobiology of this co-occurrence. Several hypothetical mechanisms of DAH in CD have been considered, such as food allergen-induced immune-complex deposition, anti-reticulin antibody-mediated alveolar basement membrane damage, and molecular mimicry of an infectious pathogen [ 75 - 77 ]. However, there has never been any histopathologic proof to support any of them.…”
Section: Reviewmentioning
confidence: 99%
“…All paediatric patients with IPH should undergo screening for celiac disease. 3,4 Therefore, the identification of hemosiderin-laden macrophages from BALF specimens is suggestive, but not diagnostic, of IPH. Moreover, another study 5 reported a large number of hemosiderin-laden macrophages were also observed in the gastric lavage of an infant boy, which could lead to an early diagnosis of IPH.…”
Section: Case Imagementioning
confidence: 99%
“…This is due to the good prognosis associated with a gluten‐free diet. All paediatric patients with IPH should undergo screening for celiac disease 3,4 . Therefore, the identification of hemosiderin‐laden macrophages from BALF specimens is suggestive, but not diagnostic, of IPH.…”
Section: Case Imagementioning
confidence: 99%
“…We have recently discussed the prevalence of autoantibodies in a cohort of adult IPH patients as reported in the literature [ 13 ]. Similar to pediatric patients, a majority of these patients had antibodies suggestive of celiac disease (CD), a combination known as Lane Hamilton syndrome (LHS) [ 12 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%